Nature of back slopping kombucha fermentation process: insights from the microbial succession, metabolites composition changes and their correlations - Liao, Ting; Li, Xiang-Ru; Fan, Li; Zhang, Bo; Zheng, Wei-Ming; Hua, Jia-Jia; Li, Li; Mahror, Norlia; Cheng, Lai-Hoong (Frontiers in Microbiology, 2024)
Kombucha, a fermented tea prepared with a symbiotic culture of bacteria and yeast (SCOBY), offers a unique and unpredictable home-brewed fermentation process. Therefore, the need for a controlled kombucha fermentation process has become evident, which requiring a thorough understanding of the microbial composition and its relationship with the metabolites produced. In this study, we investigated the dynamics of microbial communities and metabolites over a 12-day fermentation period of a conventional kombucha-making process. Our findings revealed similarities between the microbial communities in the early (0-2 days) and late (10-12 days) fermentation periods, supporting the principle of backslopping fermentation. Untargeted metabolite analysis unveiled the presence of harmful biogenic amines in the produced kombucha, with concentrations increasing progressively throughout fermentation, albeit showing relatively lower abundance on days 8 and 12.Additionally, a contrasting trend between ethanol and caffeine content was observed.Canonical correspondence analysis highlighted strong positive correlations between specific bacterial/yeast strains and identified metabolites. In conclusion, our study sheds light on the microbial and metabolite dynamics of kombucha fermentation, emphasizing the importance of microbial control and quality assurance measures in the production process.